Integrasi Maqam Tasawuf dalam Psikoterapi Islam: Pendekatan Spiritual terhadap Kesehatan Mental - Dian Siti Nurjanah; Medina Chodijah (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine five principal maqamat (spiritual stations) in Sufism—repentance (taubah), detachment (zuhud), patience (sabr), trust in God (tawakkul), and contentment (rida)—and to analyze their characteristics and therapeutic value within the framework of Islamic psychotherapy. Employing a qualitative approach through library research, this study explores classical and contemporary Sufi texts to identify the psycho-spiritual dimensions embedded in each maqam. The findings reveal that each maqam contains psychological indicators that contribute to overcoming anxiety, emotional stress, and psychosomatic disorders. Taubah serves as a foundation for spiritual purification; zuhud as detachment from worldly attachment; sabr as spiritual resilience; tawakkul as the embodiment of divine unity (tawhid); and rida as the ultimate acceptance of divine decree. Together, these maqamat form a coherent framework of spiritual therapy, highly applicable in Islamic psychotherapy practices. The primary contribution of this study lies in reinforcing Islamic spirituality-based psychotherapy through the integration of Sufi maqamat into theoretical frameworks of mental health. It also enriches interdisciplinary discourse between Sufism and psychology, and opens opportunities for developing contextual Sufi-based therapeutic approaches relevant to modern society.